The role of empathy in the service experience. Issue 2 (21st August 2019) - Tan, Adrian Heng Tsai; Muskat, Birgit; Johns, Raechel
Abstract : Purpose: The purpose of this paper is to examine the role of empathy in the student service experience. Taking a dyadic perspective, both students' and staff's perceptions are analyzed to determine if empathy matters to both actors alike; and which differences in perceptions about the role of empathy between these actors exist. Design/methodology/approach: The authors adopt a multi-method approach and used data from 256 usable survey responses from 11 higher education service providers in Singapore. Empathy was operationalized by six cognitive and affective independent variables and multiple multivariate analyses are applied, such as multivariate analysis of variance, discriminant analysis and multiple regression analysis. Findings: Results show that both students and staff alike evaluate empathy as important in the co-created service experience. The provision of individualized attention to students to positively influence student experience in learning was deemed important by both staff and students. Yet, there are also distinct differences. For students, it is essential that staff members have students' best interests at heart; for staff members, knowledge of students' needs and show of care and concern are important. Practical implications: Students and staff perceive empathy in higher education service provision differently. Interestingly, whilst staff think caring for students is important, students feel that too much care and concern from staff has a negative effect on their experience. Hence, too much care and concern might cause potential issues with the students' perception of "over-servicing" which might manifest as "spoon-feeding." Instead, students are asking for individualized and professionalized attention to be taken seriously and to be involved in the co-creation of the education service experience. Originality/value: This study advances the understanding of affective and cognitive aspects of empathy and their influence on students' service experiences.